Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) Induced Dyspepsia - Ray-Yee Yap, Paul; Goh, Khean-Lee (Current Pharmaceutical Design, 2015)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the most prescribed group of drugs in the world. They are used primarily for pain relief in chronic inflammatory joint disease and act by inhibiting enzymes COX1 and COX2 and ultimately preventing the production of active prostanoids which are required for the innate inflammatory pathway. The use of NSAIDs have been associated with the development of gastrointestinal (GI) symptoms ranging from simple dyspepsia to life threatening GI bleeds and perforations. The definition of dyspepsia has evolved over the years and this has hampered accurate studies on the prevalence of dyspepsia as different studies used varying criteria to define dyspepsia. It is now known that NSAIDs significantly increase the risk of dyspepsia.The risk of developing peptic ulcer disease vary with specific NSAIDs and dosages but there is no correlation between the symptoms of dyspepsia and underlying peptic ulcers. The pathogenesis of dyspepsia with NSAIDs is not completely understood. Peptic ulceration alone is not able to account for the majority of dyspepsia symptoms encountered by NSAIDs users. Erosive oesophagitis secondary to NSAIDs may be contributing factor to the prevalence of dyspepsia in NSAIDs users. Altered gut permeability and changes in gastric mechanosensory function due to NSAIDs may also be a contributory factor. Management of NSAID induced dyspepsia is involves a multipronged approach. Drug avoidance if possible would be ideal. Other options include using the lowest effective dose, changing to an NSAIDs with a safer GI risk profile, avoiding concurrent use with other NSAIDs or if the patient has a previous history of peptic ulcer disease, and co-prescribing with anti-secretory medications such as proton pump inhibitors. Eradication of Helicobacter pylori has a protective role against developing peptic ulcers and may also improve symptoms of NSAIDs induced dyspepsia.
Keywords: upper gastrointestinal complications